Asthma 101 for Schools: Successes and Challenges in Transitioning to Online Delivery - Nowakowski, Alexandra Catherine Hayes; Carretta, Henry Joseph; Dudley, Julie Kurlfink; Forrest, Jamie R. (Frontiers in Public Health, 2016)
Florida Asthma Program (FAP) staff worked with evaluators from the Florida State University College of Medicine (FSU) to assess participation and quality of the American Lung Association’s (ALA) Asthma 101 asthma management education program for school faculty and staff between 2011 and 2014. This included transitioning the program to an online training format for the 2013-2014 school year. Asthma 101 helps school personnel master the basics of asthma physiology and management, with content tailored specifically for K-12 educational settings. The program is assessed with questionnaires at multiple timepoints, yielding a quasi-experimental evaluation design. Evaluators reviewed quantitative data from pre-tests and qualitative and quantitative data from post-program satisfaction questionnaires. Program spreadsheets listing the dates for delivery and number of attendees were also reviewed. Overall, evaluation findings were positive. In the 2011-2012 program year, 16 different course sessions were offered, and more than half of enrolled participants came from Title I schools. A total of 228 people were trained. In the 2012-2013 program year, 19 different course sessions were offered. Enrollment totals (638) and matching pre and posttest totals (562) soundly exceeded the target metric of 425. At least 170 (27%) of a total of 638 participants could be verified as coming from the target demographic of Title I school faculty and staff. In the 2013-2014 program year, the course was offered online on a rolling basis via the Florida TRAIN course management system. Enrollment remained high, and learner outcomes remained consistently strong across all content areas for knowledge and satisfaction. A total of 406 people participated in the training; complete pre and posttest data were available for 341 of these individuals; and satisfaction data were available for 325. Of the 406 trainees, 199 (49%) reported working for Title I schools. Evaluation yielded very positive results. An overwhelming majority of participants reported finding the course consistently strong across the board, and highly impactful for their own ability to help students manage their asthma effectively. Most participants also reported that they would change/improve their asthma management behaviors in the workplace. Recommendations were developed to help expand future program reach.